Assessing the quality of life of patients with metastatic castration-resistant prostate cancer with bone metastases receiving [223Ra]RaCl2 therapy. Issue 38 (18th September 2020) - Sraieb, Miriam; Hirmas, Nader; Conrad, Rupert; Marinova, Milka; Essler, Markus; Herrmann, Ken; Ahmadzadehfar, Hojjat
Abstract : Abstract: [ 223 Ra]RaCl2 dichloride treatment in patients with metastatic castration-resistant prostate cancer (mCRPC) is associated with improved overall survival (OS) and a delay in the time to the first symptomatic skeletal-related event. The aim of this study was to evaluate the quality of life (QoL) of patients with mCRPC receiving [ 223 Ra]RaCl2 treatment using the European Organization for Research and Treatment of Cancer (EORTC) validated questionnaire form. Thirty patients with mCRPC were included in this study. The patients were administered the EORTC QLQ-C30 (version 3.0) questionnaire at 5 time points: before [ 223 Ra]RaCl2 treatment, after the first cycle, after the third cycle, after the fifth cycle, and at the end of the treatment. Median age at diagnosis was 65.2 years (range, 49.1–75.5). There was a significant 25% drop in the median alkaline phosphatase levels: 101 U/L (range, 58–594) vs. 75 U/L (39–649) before and during treatment, respectively ( P  = .003). The median dose of [ 223 Ra]RaCl2 for all patients was 4.1 MBq (range, 3.35–6.55), and the majority of patients received 5 treatment cycles (range 3–6). Seventeen patients were alive at the end of treatment (56.7%). The median OS was 26 months (range, 19.8–32.2). All of the patients filled out the questionnaires at the first 3 time points; the fourth survey included 28 patients, and only 23 patients completed the fifth questionnaire. Compared to the baseline, only the scale "role functioning" showed a temporary worsening after the first therapy cycle ( P  = .03). In subsequent cycles, its mean value rose to initial levels. All other functional and symptom scales, as well as global health status, remained constant over all 5 time points and showed no significant changes ( P  > .05). [ 223 Ra]RaCl2 therapy does not adversely impair the health-related QoL of patients with mCRPC and bone metastasis. Only patients' role functioning worsened temporarily after the first therapy cycle but stabilized in subsequent treatment cycles.